Access to knowledge and the formation of lawyer-identity: a Bernsteinian comparison of undergraduate law degrees at two UK universities of different status - Ordoyno, Hannah (2016)
In order to investigate students’ success and experience at university, this thesis compared students’ access to knowledge through the curriculum, teaching and learning (pedagogy) in Law undergraduate degrees at two UK universities of different status: a higher status ‘pre-1992’ Russell Group University (‘Global’) and a lower status ‘post-1992’ university, which is a member of the Million + Group (‘Local’). Lower-status universities recruit more students from unrepresented groups: students from ethnic minorities; those with disabilities; those who have been in local authority care; mature students; and, students from lower socio-economic groups. These students are often judged to be at a further disadvantage because their universities’ positions in higher education league tables gives the impression that the universities they are attending offer a lower standard of education than the higher status universities. This research focuses upon students’ experiences, at different universities, during their degree and, as such, contributes to the limited body of research about factors which affect student retention and success in higher education.